Microfluidic transfer of liquid interface for parallel stretching and stamping of terminal-unmodified single DNA molecules in zigzag-shaped microgrooves12. Issue 1 (15th October 2014) - Yasaki, Hirotoshi; Onoshima, Daisuke; Yasui, Takao; Yukawa, Hiroshi; Kaji, Noritada; Baba, Yoshinobu
Abstract : On-chip stretching and aligning of single DNA molecules were demonstrated using microfluidic transfer of liquid interface in zigzag-shaped microgrooves. Abstract : The molecular stretching of DNA is an indispensable tool for the optical exploration of base sequences and epigenomic changes of DNA at a single molecule level. In stretching terminal-unmodified DNA molecules parallel to each other on solid substrate, the receding meniscus assembly and capillary force through the dewetting process are quite useful. These can be achieved by pulling the substrate out of the DNA solution or sliding a droplet of DNA solution between a pair of substrates. However, currently used methods do not allow control over liquid interface motion and single-molecule DNA positioning. Here, we show a microfluidic device for stretching DNA molecules by syringing through microgrooves. The device can trap single DNA molecules at vertices of the microgrooves, which were designed as parallel zigzag lines. Different zigzag pattern depths, sizes, and shapes were studied to evaluate the adsorption possibility of DNA on the surface. The microfluidic transfer of the liquid interface stretched over 1500 DNA molecules simultaneously. The stretched DNA molecules could be stamped to a silanized surface. The device will therefore serve as a template preparation for high-resolution DNA imaging studies.